Ratio Legis Unsur Tanpa Hak Dalam Perundangan Tentang Penggunaan Senjata Tajam Di Indonesia - Fendi Anto; Febriana Nur Widyaningsih; Suratman Suratman; Moh. Muhibbin (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2022)
Law appears in accordance with the political and social configuration of a certain period. This fact indicates that the law continues to require renewal. One of the proofs that the law cannot reach people's lives which continues to develop is the emergence of Emergency Law no. 12 of 1951. The emergency law emerged as a renewal of the Republic of Indonesia Law No. 8 of 1948, and changed the Ordonnantie Tijdelijke Bijzondere Strafbepalingen (sbtl. 1948 No. 17). At certain times the emergency law was the right solution, but now the law that has not been updated can cause problems. One of the problems that arise is the ambiguity of the